2019
DOI: 10.1080/10872981.2019.1567239
|View full text |Cite
|
Sign up to set email alerts
|

Developing faculty leadership from ‘within’: a 12-year reflection from an internal faculty leadership development program of an academic health sciences center

Abstract: Most academic health sciences centers offer faculty leadership development programs (LDPs); however, the outcomes of LDPs are largely unknown. This article describes perspectives from our 12-year experience cultivating a formal faculty LDP within an academic health center and longitudinal outcomes of our LDP. Responding to faculty concerns from University of California San Francisco’s (UCSF) 2001 Faculty Climate Survey, UCSF established the UCSF-Coro Faculty Leadership Collaborative (FLC) in 2005. The FLC focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 7 publications
1
40
0
1
Order By: Relevance
“…The literature on faculty-level leadership training programs in medicine supports a strong emphasis on transformational leadership skills including change management, creating a shared vision, and transitions of leadership. 10 If the goal of leadership training during residency is to facilitate development of future physician leaders, inclusion of these advanced concepts should also be considered for early introduction by residency programs.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
“…The literature on faculty-level leadership training programs in medicine supports a strong emphasis on transformational leadership skills including change management, creating a shared vision, and transitions of leadership. 10 If the goal of leadership training during residency is to facilitate development of future physician leaders, inclusion of these advanced concepts should also be considered for early introduction by residency programs.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
“…Satisfaction with leadership programs correlated strongly with role engagement [95], with most reporting positive experiences, increased leadership competencies, newly created networks, enhanced interactions and a supportive community of practice [94,95,97À99,100]. Organisations benefitted from demonstrating commitment, which enhanced participant willingness and ability to understand how to navigate the workplace [94,95,98,99,101], also improving attitudes, engagement and retention [86,102,103]. Improved retention, professional growth, capacity and engagement in mentoring others was also noted [93,103] alongside leadership advancement [93,100,104].…”
Section: Category 4 à Leadership Developmentmentioning
confidence: 99%
“…Many studies have suggested that holding academic leadership roles such as leading a department is a favorable factor for improving teachers' innovative ability (Smith et al, 2012). Thus, the related issues of faculty leadership (Tsoh et al, 2019), academic leadership (Bikmoradi et al, 2010;Hofmeyer et al, 2015;Karaferye, 2017;Rich, 2006), department leadership, and educational leadership are the hot topics in discussing leadership in HEIs. The term professional development is used loosely to cover faculty development, instructional development, and organizational development (Diamond, 2002).…”
Section: Tl In Heismentioning
confidence: 99%